Congressional Record-Senate (Tufts Archival Research Center, 2007)
Extract from the Senate Congressional Record, March 10, 1986. Highlights section on business deductability of Federal excise taxes. Contains statement on legislation which would deny businesses the right to deduct Federal excise taxes. Claims legislation "will have a significantly negative impact on every sector of the U.S. economy." Focuses on impact it would have on the transportation industry.